Sistema de estabilización electrónico de cámara digital para fotogrametría con vehículo aéreo no tripulado - Vargas-Guevara, Andrés (Instituto Tecnológico de Costa Rica, 2016)
Mismanagement of land dedicated to agricultural activities, coupled with adverse weather conditions, generate erosion that wears the soil and pollute the surrounding water bodies. One of the methods used to quantify erosion is through runoff plots. Due to the complexity for data acquisition, they provide low precision and are characterized for been a very invasive method because of the considerable portion of land that is needed. The Agricultural Engineering and Electronic Engineering Departments, from the Costa Rica Institute of Technology, are joining efforts to create a methodology that does not have the problems involved in the use of runoff plots. The objective of this research is to use an unmanned aerial vehicle (UAV for short) that flies over and takes pictures of the terrain that has to be analyzed, and then, using photogrammetric techniques, generate digital elevation models with sufficient accuracy. A digital camera stabilization system is usually required to capture high quality pictures. The aim of this project is to develop an electronic stabilization for a digital camera, which allows to counter the movement of the UAV system. The above seeks to reduce the error associated with the change in the Euler angles as the system moves through the air, obtaining digital photographs with more reliable information and without visual distortion.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2016.
Keywords: Erosión; Fotogrametría; Cámaras digitales; Fotografías; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electrical engineering